Design of Infiltration Well to Reduce Inundation in Rawa Makmur Village, Bengkulu City - Meilani Belladona; Narlis Nasir; Endri Agustomi (Journal of Applied Sciences and Advanced Technology, 2018)
Rawa Makmur Village, especially Merpati I, has an area of 3.6 hectares, has experienced land use changes of 30% in the last 3 years. The purpose of this study is to design infiltration wells to reduce inundation that often occurs in this region. The data used are primary data (soil sampling and laboratory testing) and secondary data (rainfall data, land use data and other supporting data) that are processed using hydrological analysis and hydraulic analysis. Based on the results of data processing obtained the intensity of rainfall with a 20-year return period is 2.56 mm/hour and the flood discharge plan is 0.01229 m3/s. The household debit is 0.212 m3/s, the roof discharge is 0.00000037 m3/s, so the total debit that must be reduced is 0.222 m3/s. The soil sample at the study location is taken and tested in the laboratory. The test results show the soil permeability coefficient is 2.630 x 10-4 m3/s. Infiltration discharge into the soil is 0.000152 m3/s, then the reduced discharge is 0.2218 m3/s. Based on the analysis results obtained the design of infiltration wells with a diameter of 1 meter and a depth of 2.2 meters. One well was effectively used for 2 houses with a reduction of 0.2218 m3/s with a reduction time of 1,297 minutes.